The role of CAR-T cells in the immunotherapy of B-cell acute lymphoblastic leukemia: a systematic review (Research, Society and Development, 2023)
Introduction: Therapy with CAR-T cells for hematological malignancies, especially B cells, has shown promising results and has become an alternative for the clinical practice of acute lymphoblastic leukemia. Objective: To evaluate the efficacy, safety and applicability of CAR-T cell therapy in the immunotherapy of B-cell acute lymphoblastic leukemia (B-ALL). Methodology: This is a systematic review study guided by the PRISMA method. PubMed and VHL databases were used to search for phase I and II clinical trials, published between 2013 and 2023, with the descriptors “CAR-T cells” or “chimeric antigen receptor” and “immunotherapy” or “treatment”. and “acute lymphoblastic leukemia” and “B cells”. Results: 2,204 reports were identified. Of these, 13 met the eligibility criteria and were included in the study. High response rates have been observed, with complete and morphological remissions ranging from 40-100%. Occurrence of cytokine release syndrome of any degree between 80-85%, severe syndrome of 16-26% and severe neurotoxic effects of 28-42% among patients, although immune-mediated and favorable to the safety of therapy. Conclusion: CAR-T cell immunotherapy demonstrated potent antileukemic activity, with a well-defined toxicity profile and favorable therapy safety, leading to the approval of a CAR-T cell product for the treatment of relapsed/refractory ALL-B.